RISK FACTORS OF PEDICLE FIXATION INSTABILITY AT PATIENTS WITH DEGENERATIVE LUMBAR SPINE PATHOLOGY - A. E. Bokov; S. G. Mlyavykh; A. Ya. Aleynik; A. A. Bulkin; M. V. Rasteryaeva (Бюллетень сибирской медицины, 2016)
Objective. To assess risk factors оf pedicle screw instability after decompression and fusion in patients with degenerative lumbar spine disease.Materials and methods. This is a prospective non-randomized study, the results of 130 surgical interventions with pedicle instrumentation in patients with degenerative lumbar spine diseases were studied. Minimal follow up period accounts for 18 months. Before intervention computed tomography (CT) was applied and cancellous bone radiodensity was measured.Patients were treated with nerve root decompression and pedicle screw fixation stand-alone or with lumbar interbody fusion. During follow-up period computed tomography was applied and cases with evidence of pedicle screw loosening were detected. Radiodensity of cancellous bone, extension of fixation, extensiveness of decompression, application of interbody fusion, incomplete vertebra body reduction and heterogeneity of studied group were taken into account as potential risk factors of implant instability development. The correlation between pedicle screws loosening rate and mentioned predictors was estimated using logistic regression analysis.Results. Radiodensity of vertebra body cancellous bone getting decreased, the increase number of fixed levels and extensiveness of facet joints and ligaments resection are associated with the increased risk of a screw loosening development. Laminectomy, interbody fusion, altered biomechanics associated with incomplete vertebra body reduction and L5–S1 segment included into fixed zone did not have a significant influence on pedicle screws loosening rate. Bias related to heterogeneity of studied group was also insignificant. Goodness-of-fit of estimated general logistic regression model: № 2 = 67,57851; p < 0,0001. This model classified correctly 81,5% cases with sensitivity and specificity of 77,4% and 85,3% respectively.Conclusion. Radiodensity of a vertebra cancellous bone, number of fixed levels and extensiveness of facet joints and ligaments resection during decompression are significant predictors for pedicle screws loosening development. The detected risk factors should be taken into account in preoperative planning especially in elderly patients.